A política de conservação do patrimônio cultural em Maringá-PR (1987-2008) - Friedrich, Veroni (2010)
Maringa, in the North of Paraná, was founded on 10 May 1947. Since its foundation there was an intention to preserve the city's memory. In 1964 a museum was criated named "Museu do Pioneiro". In 1972 the people who arrived at Maringá between 1940 and 1950 received the titie of pioneer. In 1984 the memory project was established and in 1987 the SPHAN - Serviço do Patrimônio Histórico de Maringá started to work. The objective of this institution was to select and manage the cultural heritage of the city. The aim of this research is to analyze the cultural heritage management. The entire research is based on photographs, newspapers, laws, acts, decrees, letters and other law documents. This whole set of documents are analyzed through methodological assumptions and offers an interpretation of the cultural heritage policy in Maringá.